Factor exposure variation and mutual fund performance - Manuel Ammann; Sebastian Fischer; Florian Weigert (University of Cologne, Centre for Financial Research (CFR), 2020)
We investigate the relationship between a mutual fund's variation in factor exposures and its future performance. Using a dynamic state space version of Carhart (1997)'s four factor model to capture factor variation, we find that funds with volatile factor exposures underperform funds with stable factor exposures by 147 basis points p.a. This underperformance is neither explained by volatile factor loadings of a fund's equity holdings nor driven by a fund's forced trading through investor flows. We conclude that fund managers voluntarily attempt to time factors, but they are unsuccessful at doing so.
Keywords: G11; G14; G20; G23; 330; Mutual Fund; Market Timing; Factor Timing; Factor Exposure; Kalman Filter; Underperformance